1989
DOI: 10.1113/jphysiol.1989.sp017879
|View full text |Cite
|
Sign up to set email alerts
|

Further observations on the behaviour of ouabain‐insensitive sodium efflux towards proctolin in barnacle muscle fibres.

Abstract: SUMMARY1. A further study has been made of the stimulatory action of proctolin on the ouabain-insensitive Na+ efflux in single muscle fibres from the barnacle, Balanus nubilus.2. (i) Strontium (Sr2+) behaves as a substitute for external Ca2+. In this case, however, the response to proctolin fails to decay. (ii) Injection of Sr2+ stimulates the ouabain-insensitive Na+ efflux. This effect is mimicked by injecting Ca2 .3. Depolarization of the fibre membrane with 30 and 100 mM-external K+ augments the response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…In crayfish skeletal muscle, Bishop et al (199 1) showed that proctolin modulates the voltage-dependent activation of Ca *+ channels, effects that would have been masked by the Cd*+ we used. Finally, in barnacle muscle fibers proctolin activates a ouabain-insensitive Na+ efflux (Bittar and Nwoga, 1989) an effect that would have been masked by the low Na+ influx due to the presence of TTX in our preparations. However, although it is certainly possible that the proctolin target neurons display an additional proctolin response, we saw no indication that any of the pharmacological agents we used to isolate the proctolin current for study influenced the amplitude or the character of the proctolin response.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In crayfish skeletal muscle, Bishop et al (199 1) showed that proctolin modulates the voltage-dependent activation of Ca *+ channels, effects that would have been masked by the Cd*+ we used. Finally, in barnacle muscle fibers proctolin activates a ouabain-insensitive Na+ efflux (Bittar and Nwoga, 1989) an effect that would have been masked by the low Na+ influx due to the presence of TTX in our preparations. However, although it is certainly possible that the proctolin target neurons display an additional proctolin response, we saw no indication that any of the pharmacological agents we used to isolate the proctolin current for study influenced the amplitude or the character of the proctolin response.…”
Section: Resultsmentioning
confidence: 99%
“…Proctolin itself has been proposed to act via a CAMP-dependent mechanism (Jennings et al, 1983;Orchard et al, 1989;Bishop et al, 199 1) and via a G-protein (Bittar and Nwoga, 1989) in other preparations. The slow nature of the proctolin response we have described (see Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The species of barnacles, the methods of dissection, cannulation, microinjection and counting of 22Na+ activity in the effluent and in the fibre, as well as the measurement of the membrane potential, were essentially the same as those described previously (Bittar & Nwoga, 1989b). Solutions with varying concentrations of Ca2+ were prepared by raising or reducing NaCl in 264 EFFECT OF PHORBOL DIBUTYRATE Na+ EFFLUX osmotically equivalent amounts.…”
Section: Methodsmentioning
confidence: 99%
“…To prepare solutions of furosemide, piretanide and bumetanide in millimolar concentrations, methanol was used as the solvent and its final concentration in ASW was 1 %. Changes in myoplasmic free Ca2+ were monitored with the Ca2+_ sensitive photoprotein, aequorin, as described by Ashley & Ridgway (1970) in this preparation and by Bittar & Nwoga (1989b). All experiments were performed at room temperature (between 22 and 24 0C).…”
Section: Methodsmentioning
confidence: 99%
“…In barnacle muscle fibers, for example, a proctolin response (in this case, a proctolin-stimulated, ouabain-insensitive Na2+ efflux) was found to be eliminated with Cd*+ and Co2+ and correlated with increased cytosolic free CaZ+ (which was measured with aequorin; Bittar and Nwoga, 1989). Similar Ca*+ channel blockers were found to block proctolin-induced contractures in a number of other muscle preparations, including Limuhs heart muscle (Watson and Hoshi, 1985) lobster opener muscle (Schwartz et al, 1980), and cockroach hypemeural muscle (Hertel and Penzlin, 1986).…”
Section: Discussionmentioning
confidence: 97%